Optimal capacitor placement in radial distribution system using harmony search algorithm [electronic resource] - Rusdee Azeem Mohamad Rusli, 1986-
Thesis (Sarjana Kejuruteraan (Elektrik - Kuasa)) - Universiti Teknologi Malaysia, 2012